FGF21 alleviates pulmonary hypertension by inhibiting mTORC1/EIF4EBP1 pathway via H19. Issue 10 (19th April 2022) - Li, Xiuchun; Zhang, Yaxin; Su, Lihuang; Cai, Luqiong; Zhang, Chi; Zhang, Jianhao; Sun, Junwei; Chai, Mengyu; Cai, Mengsi; Wu, Qian; Zhang, Chi; Yan, Xiaoqing; et al.
Abstract: Long non‐coding RNAs (lncRNAs) play a significant role in pulmonary hypertension (PH). Our preliminary data showed that hypoxia‐induced PH is attenuated by fibroblast growth factor 21 (FGF21) administration. Therefore, we further investigated the regulatory role of long non‐coding RNAs in PH treated with FGF21. RNA sequencing analysis and real‐time PCR identified a significantly up‐regulation of the H19 after FGF21 administration. Moreover, gain‐ and loss‐of‐function assays demonstrated that FGF21 suppressed hypoxia‐induced proliferation of pulmonary artery smooth muscle cells partially through upregulation of H19. In addition, FGF21 deficiency markedly exacerbated hypoxia‐induced increases of pulmonary artery pressure and pulmonary vascular remodelling. In addition, AAV‐mediated H19 overexpression reversed the malignant phenotype of FGF21 knockout mice under hypoxia expose. Further investigation uncovered that H19 also acted as an orchestra conductor that inhibited the function of mechanistic target of rapamycin complex 1 (mTORC1) by disrupting the interaction of mTORC1 with eukaryotic translation initiation factor 4E–binding protein 1 (EIF4EBP1). Our work highlights the important role of H19 in PH treated with FGF21 and suggests a mechanism involving mTORC1/EIF4EBP1 inhibition, which may provide a fundamental for clinical application of FGF21 in PH.